A COMPARATIVE STUDY BETWEEN WATER-GAP AND AIR-GAP DISTILLATION MEMBRANES FOR REMOVAL OF SALTS FROM SALINE WATER BY DESALINATION METHOD - LAURENTIU TATARU; VALENTIN NEDEFF; NARCIS BARSAN; MIRELA PANAINTE-LEHADUS; EMILIAN MOSNEGUTU; DANA CHITIMUS; FLORINA FABIAN (Journal of Engineering Studies and Research)
The water deficit for consumption in various daily activities is more pronounced especially in countries where rainfall is low or in those areas where water demand is higher than available resources. This paper is a comparison between the airgap and water-gap distillation method. The results of the study have shown that the water-based distillation method can be more efficient, as the volume of permeate obtained is higher in relation to the increase in the flow temperature.The results obtained as well as the comparison of the advantages related to the two membrane distillation processes will be presented in the present paper.